2016
DOI: 10.1111/1752-1688.12456
|View full text |Cite
|
Sign up to set email alerts
|

Continental‐Scale River Flow Modeling of the Mississippi River Basin Using High‐Resolution NHDPlus Dataset

Abstract: As a key component of the National Flood Interoperability Experiment (NFIE), this article presents the continental scale river flow modeling of the Mississippi River Basin (MRB), using high‐resolution river data from NHDPlus. The Routing Application for Parallel computatIon of Discharge (RAPID) was applied to the MRB with more than 1.2 million river reaches for a 10‐year study (2005‐2014). Runoff data from the Variable Infiltration Capacity (VIC) model was used as input to RAPID. This article investigates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 62 publications
(108 reference statements)
1
81
0
Order By: Relevance
“…() and Tavakoly et al . (), one such model is the light‐weight and computationally efficient RAPID river routing model which has been implemented, among other domains, over the Texas Gulf Coast and Mississippi River basins. The development of these models has presented an opportunity to systematically link atmospheric and land surface processes, over large domains, to catchment scale hydrologic and hydraulic processes.…”
Section: Existing Forecasting and Modeling Capabilitiesmentioning
confidence: 99%
“…() and Tavakoly et al . (), one such model is the light‐weight and computationally efficient RAPID river routing model which has been implemented, among other domains, over the Texas Gulf Coast and Mississippi River basins. The development of these models has presented an opportunity to systematically link atmospheric and land surface processes, over large domains, to catchment scale hydrologic and hydraulic processes.…”
Section: Existing Forecasting and Modeling Capabilitiesmentioning
confidence: 99%
“…Using parallel computing, the flow can be simulated quickly throughout a basin with a high density of stream segments. RAPID has been implemented for regions of varying scales including France (David et al ., ), the San Antonio and Guadalupe basins in Texas (David et al ., ; Tavakoly et al ., ), the Texas Gulf Coast region (David et al ., ), and the Mississippi River Basin (MRB) (Tavakoly et al ., ). Tavakoly et al .…”
Section: Introductionmentioning
confidence: 98%
“…Tavakoly et al . () found that RAPID can be deployed with reasonable accuracy over the entire MRB when major dam operations are included, but the results are more accurate in the more humid eastern part of the MRB. However, RAPID only simulates the flow rate within each reach; it does not simulate flood inundation area.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of these parameters is explained in [1] and [4] and the estimated values can be improved through optimization. Examples of possible cost functions that can be used to optimize these parameters are found in [1] [3] and [5]. The second routing component we evaluate in this study is the one implemented in the Hillslope-Link hydrologic Model (HLM) developed and used by the Iowa Flood Center (IFC).…”
Section: Introductionmentioning
confidence: 99%
“…This routing component is nonlinear and accounts for the momentum equation in a simplified form ( [6] [7] and [8]), and the stream velocity is determined based on the nonlinear relationship between the discharge and the served area ( [9] [10]). Similar to [1] [11] and [5] we do not account in this study for lateral flows to the channel in our calculation for the sake of simplicity and since our sub-catchment sizes are small. This means we assume the runoff depth immediately enters the streams in their corresponding upstream junctions before the channel routing takes place.…”
Section: Introductionmentioning
confidence: 99%